LBK realpolitik : an archaeometric study of conflict and social structure in the Belgian early Neolithic - Golitko, Mark, (Archaeopress archaeology., 2015)
The causes and consequences of violence and warfare have long interested social scientists, historians, and philosophers. While economic motivations for conflict are among the most commonly discussed drivers of human violence, prehistorians have often downplayed economic factors when studying non-state society. This volume explores linkages between conflict and socioeconomic organization during the early Neolithic of eastern Belgium (c.5200-5000 BC), using compositional analysis of ceramics from Linienbandkeramik villages to assess production organization and map intercommunity connections against the backdrop of increasing evidence for conflict.